Improving Surgical and Anaesthesia Practice: Review of the Use of the WHO Safe Surgery Checklist in Felege Hiwot Referral Hospital, Ethiopia. Issue 1 (1st March 2017) - Ellis, Ryan; Izzuddin Mohamad Nor, Ahmad; Pimentil, Iona; Bitew, Zebenaye; Moore, Jolene
Abstract : Development of surgical and anaesthetic care globally has been consistently reported as being inadequate. The Lancet Commission on Global Surgery highlights the need for action to address this deficit. One such action to improve global surgical safety is the introduction of the WHO Surgical Checklist to Operating Rooms (OR) around the world. The checklist has a growing body of evidence supporting its ability to assist in the delivery of safe anaesthesia and surgical care. Here we report the introduction of the Checklist to a major Ethiopian referral hospital and low-resource setting and highlight the success and challenges of its implementation over a one year period. This project was conducted between July 2015 and August 2016, within a wider partnership between Felege Hiwot Hospital and The University of Aberdeen. The WHO Surgical Checklist was modified for appropriate and locally specific use within the OR of Felege Hiwot. The modified Checklist was introduced to all OR's and staff instructed on its use by local surgical leaders. Assessment of use of the Checklist was performed for General Surgical OR in three phases and Obstetric OR in two phases via observational study and case note review. Training was conduct between each phase to address challenges and promote use. Checklist utilisation in the general OR increased between Phase I and 2 from 50% to 97% and remained high at 94% in Phase 3. Between Phase I and 2 partial completion rose from 27% to 77%, whereas full completion remained unchanged (23% to 20%). Phase 3 resulted in an increase in full completion from 20% to 60%. After 1 year the least completed section was "Sign In" (53%) and "Time Out" was most completed (87%). The most poorly checked item was "Site Marked" (60%). Use of the checklist in Obstetrics OR increased between Phase I and Phase II from 50% to 100% with some improvement in partial completion (50% to 60%) and a notable increase in full completion (0% to 40%). The least completed section was "Time Out" (50%) and "Sign In" was the most completed (90%). The most poorly checked item was "Recovery Concerns" (70%). There was considerable enthusiasm for use of the checklist among staff. The greatest challenge was communication difficulties between teams and high staff turnover. This study records a locally driven, successful introduction of the WHO Surgical Safety Checklist modified for the specific locale and illustrates an increase in use of the checklist over a one year period in both General Surgical and Obstetric OR's. Local determination and ownership of the Checklist with regular intervention to promote use and train users contributed to this success.